Anxiety, depression, and PTSD during lockdown: A longitudinal study - Vicente Escudero, José Luis (2022)
Background: The period of lockdown has brought negative psychological consequences worldwide. In particular, problems of anxiety, depression and stress have been exacerbated. Aim: This research analyses the evolution and relationship of anxiety, depression and PTSD at the beginning and end of lockdown and at the beginning of the so-called “new normality” in Spain. Method: The present research assessed a sample of 67 adults from the general population aged 18-56 years from the Region of Murcia, Spain, using the STAI questionnaire for anxiety, BDI-II for depression and EGS-R for PTSD. The sample was collected longitudinally between 20th and 22th March 2020 (T1), 11th and 18th May 2020 (T2), and 1st and 9th September 2020 (T3). Results: Elevated levels of depression were found to be a risk factor for increased PTSD symptomatology during lockdown. Prevalences ranged across the three measures from 10.5% - 27.3% for state anxiety, 22.4% - 28.3% for depression and 18.4% - 21.2% for PTSD. In addition, PTSD, anxiety and depression decreased over the time of lockdown; however, cluster analysis showed that one group of subjects increased their levels of PTSD over the time of lockdown. Conclusions: The general population has been significantly affected in their mental health during the pandemic, reflecting a need for adequate psychological support to address these problems.